1978
DOI: 10.1243/jmes_jour_1978_020_008_02
|View full text |Cite
|
Sign up to set email alerts
|

Further Investigation of Conical Diffusers with Annular Injection

Abstract: A comprehensive investigation is made, for a wide range of incompressible flows, into the merits of annular injection as a means of obtaining a high-performance diffuser with short axial length. Results show that injection yields considerable improvements in both the quality of the discharging flow and the magnitude of the pressure recovery. Accordingly, the technique is strongly recommended when a short, high-performance diffuser is required and when a suitable secondary supply is available. Recommendations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…They also redefined the coefficient of pressure recovery to account for the injection energy. Duggins et al [6] have shown that an axial annular jet is better than a tangential annular jet for conical diffusers. Boundary layer control by suction has been attempted by Ackeret [7] and Furuya et al [8] at the diffuser inlet and they have succeeded in achieving higher performance for wide-angled conical diffusers.…”
Section: Introductionmentioning
confidence: 99%
“…They also redefined the coefficient of pressure recovery to account for the injection energy. Duggins et al [6] have shown that an axial annular jet is better than a tangential annular jet for conical diffusers. Boundary layer control by suction has been attempted by Ackeret [7] and Furuya et al [8] at the diffuser inlet and they have succeeded in achieving higher performance for wide-angled conical diffusers.…”
Section: Introductionmentioning
confidence: 99%